Analisis Pengaruh Informasi Produk Ramah Lingkungan dan Budaya Ramah Lingkungan Terhadap Perilaku Ramah Lingkungan - Brian Gregory Adhihendra; Reno Firman Anriza Hirianto (Jurnal Bisnis dan Ekonomi, 2021)
The development of environmental sustainability issues at this time is one of the things that is discussed in the context of the business environment. Environmental issues include environmental sustainability, waste pollution, and are also related to the use of products with minimal emissions and pollutants. This research focuses on the discussion of environmental issues where the information aspects of green information products, green culture, and green behavior are the focus of discussion. Researchers built this study using quantitative techniques with valid sample data of 200 respondents from all over Indonesia who understood and chose to use Tupperware's tumbler products. The data analysis used was AMOS 21. The results of the analysis carried out then showed that green products information and green culture had a positive and significant effect on green behavior.